Post-stroke BDNF concentration changes following physical exercise : A systematic review (2018)
Background: Research over the last two decades has highlighted the critical role of Brain-derived neurotrophic factor (BDNF) in brain neuroplasticity. Studies suggest that physical exercise may have a positive impact on the release of BDNF and therefore, brain plasticity. These results in animal and human studies have potential implications for the recovery from damage to the brain and for interventions that aim to facilitate neuroplasticity and, therefore, the rehabilitation process. Purpose: The aim of this study was to carry out a systematic review of the literature investigating how aerobic exercises and functional task training influence BDNF concentrations post-stroke in humans and animal models. Data Sources: Searches were conducted in PubMed (via National Library of Medicine), SCOPUS (Elsevier), CINAHL with Full Text (EBSCO), MEDLINE 1946-present with daily updates (Ovid) and Cochrane. Study Selection: All of the database searches were limited to the period from January, 2004 to May, 2017. Data Extraction: Two reviewers extracted study details and data. The methodological quality of the studies that used animal models was assessed using the ARRIVE Guidelines, and the study that evaluated human BDNF was assessed using the PEDro Scale. Data Synthesis: Twenty-one articles were included in this review. BDNF measurements were performed systemically (serum/plasma) or locally (central nervous system). Only one study evaluated human BDNF concentrations following physical exercise, while 20 studies were experimental studies using a stroke model in animals. A wide variation was observed in the training protocol between studies, although treadmill walking was the most common type of intervention among the studies. Studies were of variable quality: the studies that used animal models scored from 8/20 to 15/20 according to the ARRIVE Guidelines. The only study that evaluated human subjects scored 5/10 according to the PEDro scale and, which indicates a quality classified as "fair". Conclusions: The results of the current systematic review suggest that aerobic exercise promotes changes in central BDNF concentrations post-stroke. On the other hand, BDNF responses following functional exercises, such as reaching training and Constraint Induced Movement Therapy (CIMT), seem to be still controversial. Given the lack of studies evaluating post-stroke BDNF concentration following physical exercise in humans, these conclusions are based on animal work. © 2018 Alcantara, García-Salazar, Silva-Couto, Santos, Reisman and Russo.